The Evaluation of Prefabricated Vertical Drain (PVD) Installation Effect on Soft Soil Physical and Mechanical Properties - Sari, Undayani Cita; Wardani, Sri Prabandiyani Retno; Pardoyo, Bambang; Admojo, Danang Dwi; Rizqullah, Mochammad Kemal; Hussein, Muhammad Fahri (Aceh International Journal of Science and Technology, 2025)
The purpose of the Yogyakarta - Bawen Toll Road construction was to improve connectivity between Yogyakarta and Semarang. However, during its construction, soft soil problems were found, so Prefabricated Vertical Drains (PVD) were installed. The installation of PVD aims to increase the rate of pore water discharge from the soil, thereby compacting it and enhancing its bearing capacity. Changes in soil material parameters also accompany this increase in bearing capacity. This study was conducted to analyze the effect of PVD installation on the physical and mechanical properties of the soil. The analysis was conducted by comparing soil investigation data before and after the PVD installation. Soil sample data were collected from the Yogyakarta-Bawen Toll Road, STA 4+500, specifically at BH 17. The physical properties under review are water content, wet unit weight, soil specific gravity, Atterberg limits, and changes in particle composition as determined by grain size analysis. Meanwhile, changes in the mechanical properties of the soil include pre-consolidation pressure, compression index, recompression index, consolidation coefficient, and volume compressibility. Undrained shear strength parameters were measured using an unconfined compression test to identify the soil's bearing capacity. The results show changes in physical and mechanical parameters before and after PVD installation. Overall, the most critical aspect of the accelerated consolidation method for physical parameters is a decrease in water content of 13% to 37% compared to the pre-PVD installation condition. Meanwhile, changes in the consolidation parameters, as well as a decrease in unconfined compressive strength of 2% to 12%, are also observed. This occurs for various reasons, one of which is the relationship between the completion time of the consolidation process and the consolidation process. However, the soil classification remained the same, according to the USCS, as a very stiff soil type